Aerobic, Resistance, and Combination Training on Health-Related Quality of Life: The STRRIDE-AT/RT Randomized Trial - Collins, Katherine A.; Fos, Liezl B.; Ross, Leanna M.; Slentz, Cris A.; Davis, Paul G.; Willis, Leslie H.; Piner, Lucy W.; Bateman, Lori A.; Houmard, Joseph A.; Kraus, William E. (Frontiers in Sports and Active Living, 2021)
Purpose: The main purpose of this study was to determine the differential effects of aerobic training (AT), resistance training (RT), and a combination of aerobic and resistance training (AT/RT) on changes in self-rated HrQoL measures, including the Short-Form 36 (SF-36) survey and Satisfaction with Physical Function and Appearance survey. We also sought to determine if combination training (AT/RT) has a more or less additive effect compared to AT or RT alone on self-rated HrQoL measures. Materials and Methods: Participants (n = 137) completed one of three 8-month exercise interventions: (1) AT: 14 kcal exercise expenditure per kg of body weight per week (KKW; equivalent to roughly 12 miles/week) at 65–80% of peak oxygen consumption; (2) RT: 3 days per week, 8 exercises, 3 sets per exercise, 8–12 repetitions per set; (3) AT/RT: full combination of the AT and RT interventions. The SF-36 survey, Satisfaction with Physical Function and Appearance survey, physical fitness, and anthropometrics were assessed at baseline and post-intervention. Paired t-tests determined significant pre- vs. post-intervention scores within groups (p < 0.05). Analyses of covariance determined differences in change scores among groups (p < 0.05). Results: On average, participants were 49.0 ± 10.6 years old, obese (BMI: 30.6 ± 3.2 kg/m2), female (57.7%), and Caucasian (84.7%). Following the 8-month intervention, exercise groups improved peak VO2 (all groups), strength (RT and AT/RT), and anthropometric measures (AT and AT/RT). For the SF-36, RT (p = 0.03) and AT/RT (p < 0.001) significantly improved their physical component score; only AT/RT (p < 0.001) significantly improved their mental component score. Notably, all groups significantly improved both their satisfaction with physical function and appearance scores (All Groups: p < 0.001 for both outcomes). Conclusions: We found that aerobic, resistance, or combination exercise training improves several components of self-rated HrQoL, including physical function, appearance, and mental well-being. Clinical Trial Registration: No. NCT00275145.